2004
DOI: 10.1073/pnas.0403854101
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory receptor surface expression is driven by association with the β2-adrenergic receptor

Abstract: Olfactory receptors (ORs) comprise more than half of the large class I G protein-coupled receptor (GPCR) superfamily. Although cloned over a decade ago, little is known about their properties because wild-type ORs do not efficiently reach the cell surface following heterologous expression. Receptor-receptor interactions strongly influence surface trafficking of other GPCRs, and we examined whether a similar mechanism might be involved in OR surface expression. Olfactory neurons are known to express ␤-adrenergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 42 publications
5
79
1
Order By: Relevance
“…In previous confocal studies, we noted that the ␤ 2 -AR did not appear to enhance the surface localization of two ORs that are distantly related to M71: hOR17-40 and rat I7 (16). Similarly, in the current analysis, co-expression with ␤ 2 -AR, P2Y 1 R, P2Y 2 R, or A 2A R did not significantly alter hOR17-40 or rat I7 plasma membrane expression as assessed in luminometer assays (Fig.…”
Section: Specificity Of or Interactions With Othersupporting
confidence: 46%
See 4 more Smart Citations
“…In previous confocal studies, we noted that the ␤ 2 -AR did not appear to enhance the surface localization of two ORs that are distantly related to M71: hOR17-40 and rat I7 (16). Similarly, in the current analysis, co-expression with ␤ 2 -AR, P2Y 1 R, P2Y 2 R, or A 2A R did not significantly alter hOR17-40 or rat I7 plasma membrane expression as assessed in luminometer assays (Fig.…”
Section: Specificity Of or Interactions With Othersupporting
confidence: 46%
“…We previously found that ACP stimulation of wild type M71 (WT-M71) expressed in HEK-293 cells did not result in detectable receptor signaling, consistent with the lack of receptor expressed at the plasma membrane, but stimulation of WT-M71 co-expressed with ␤ 2 -AR did result in significant cAMP generation (16). These studies demonstrated that when in complex with ␤ 2 -AR, heterologously expressed WT-M71 can signal via cAMP generation, as has been reported for many examples of odorant-induced signaling in native OSNs (1,34).…”
Section: Activation Of the Mapk Pathway In Response To Agonist Stimulmentioning
confidence: 99%
See 3 more Smart Citations